Modeling and simulation of the radiolytic deuterium and oxygen generation in heavy water reactors - Mahdi Shadman, Mohammad; Ghazanfari, Valiyollah; Amini, Younes; Mansourzadeh, Fatemeh; Taheri, Armin (Nuclear engineering and design, 2023)
•The kinetic model of heavy water radiolysis, including segregated and lumped models, was developed.•From the safety point of view, the segregated model overpredicts the amount of produced deuterium and oxygen in the gas phase compared to the lumped model.•Adding deuterium to heavy water at an optimum value prevents reaching the concentration of deuterium in the gas phase to the critical values. This study developed the kinetic model of heavy water radiolysis, including segregated and lumped models. The concentration of the radiolytic volatile species in the gas phase of the pressurizer was calculated based on the radiolytic concentration of species in the liquid phase. The MATLAB ode15s, as an appropriate solver, was adopted to solve the stiff kinetic ODE equations of two models. The radiolysis model and solver were validated by comparing the results in the liquid phase in the lumped model with the published FACSIMILE code. From the safety point of view, the segregated model overpredicts the amount of produced deuterium and oxygen in the gas phase compared to the lumped model. Moreover, the result indicated that concentrations in some reactor regions of the segregated model might be close to critical concentration limits for the liquid phase, while the lumped model does not demonstrate this behavior. The ability of the segregated model as a reliable model to predict the effect of parameters such as pH (5–9), initial concentration of deuterium and oxygen (0–400 ppb), and the temperature (20 to 90 °C) was studied. The model results illustrated that decreasing pH and initial oxygen concentration, in contrast to temperature in the studied range, could reduce the D2 and O2 stable concentration in the gas phase. Adding deuterium to heavy water at an optimum value (30 ppb subject to 200 ppb initial concentration of oxygen) prevents reaching the concentration of deuterium in the gas phase to the critical values. Increasing the initial concentration of deuterium in heavy water can also control the oxidizing and corrosive environments.